Application of social media tools for project management in Rwanda - Sunday Dosumu, Oluwaseun; Oke, Ayodeji; Gbeminiyi Dosumu, Oluwaseye (Ethiopian Journal of Science and Technology, 2025)
The construction industry, both in developed and developing countries, has increasingly adopted social media tools to improve project management. However, there is a notable lack of documentation regarding the awareness, adoption, and application of these tools in the construction sector of developing countries, particularly in Rwanda. This study aims to investigate the level of awareness, adoption, and application of social media tools in construction projects. To achieve this, we employed a survey research design, administering closed-ended questionnaires to construction professionals in Rwanda, supplemented by unstructured interviews to clarify responses as needed. The findings indicate that respondents are generally aware of and have adopted social media tools for construction project management. Furthermore, a direct correlation exists between the level of awareness and the level of adoption of these tools. However, significant differences were observed between consultants and contractors concerning their awareness and adoption rates. The primary applications of social media tools identified in the study include information exchange and storage, organizational cooperation, marketing, knowledge sharing, employment opportunities, networking, and the creation of project groups. Based on these findings, the study recommends that professional bodies enhance awareness by organizing conferences, seminars, and meetings to discuss the applications and benefits of social media tools in construction projects. Additionally, project consultants should be encouraged to recommend appropriate social media tools to project bidders. Governments and policymakers should consider incentivizing effective users of these tools within the construction sector. Lastly, academics should be encouraged to devote more research efforts to exploring the specific applications, benefits, and challenges of adopting social media tools in the construction industry.